MEASUREMENT IN MECHANICAL SYSTEMS - Izhari Izni Mazali, editor 638274; Zul Hilmi Che Daud, editor 327947; Izhari Izni Mazali, contributor 638274; Zul Hilmi Che Daud, contributor 327947; Mohamad Fazrin Mohd. Lutfi, contributor 638278; Mohd. Kameil Abdul Hamid, contributor 614804; Mat Hussin Abu Talib, contributor 638279; Muhammad Nur Fitri Noorazhar, contributor 638280; Akmal Fahrudin, contributor 638287; Zainab Asus, contributor 323406; Kamalraj Sundralingam, 1996-, contributor 625427; Saiful Anuar Abu Bakar, contributor 352264; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2021)
Includes bibliographical references and index.